Integrating Disaster Risk Management and Archival Frameworks for Safeguarding Citizens' Vital Records - Martino, Martino (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
Citizen’s vital records contain information value, proof of important life events, and legal and binding ownership of assets. Disaster risk management rarely calculates damage and loss of vital records due to disasters. This article presents a comprehensive review of records protection practices designed to ensure the preservation and accessibility of citizens' vital records. This study provides a comprehensive review of practices for protecting vital records to ensure their preservation and accessibility. Using a qualitative methodology, the research examines the integration of disaster risk management and records management within the framework of the Records Continuum concept. The study identifies critical processes in protecting vital records, including prevention, mitigation, response, and recovery. It highlights the need for a tailored approach at the individual level, considering community awareness, infrastructure availability, and resource limitations. Factors such as susceptibility to natural disasters, inadequate infrastructure, low public awareness, and financial constraints exacerbate the risks to these records. Consequently, protection strategies must account for the socio-economic, physical, and cultural contexts of the affected populations. The findings emphasize that safeguarding vital records is a shared responsibility, involving not only governments and archival institutions but also active community participation. By integrating disaster risk management principles with archival frameworks, this research offers actionable insights for enhancing record preservation practices globally.